2020
DOI: 10.1016/j.jcrysgro.2020.125621
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic mineral precipitation from potable water on heat transfer surfaces

Abstract: This is a repository copy of Inorganic mineral precipitation from potable water on heat transfer surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
(23 reference statements)
0
4
0
1
Order By: Relevance
“…The formation of inorganic scale is thermodynamically possible when the aqueous solution is supersaturated with one of the sparingly soluble salts such as calcium carbonate CaCO3, sulphate salts of calcium, magnesium hydroxide Mg(OH)2, etc [1]. These deposits increase the resistance to heat transfer and reduce flow area of the working fluids in industrial, commercial and domestic systems [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of inorganic scale is thermodynamically possible when the aqueous solution is supersaturated with one of the sparingly soluble salts such as calcium carbonate CaCO3, sulphate salts of calcium, magnesium hydroxide Mg(OH)2, etc [1]. These deposits increase the resistance to heat transfer and reduce flow area of the working fluids in industrial, commercial and domestic systems [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…SO 2À 4 showed more variations than that of Cl À for all the kettles throughout the seven runs. Gailani et al (2020) have reported that as the boiling continues, the chloride ion content and salinity increase with the volume of evaporated water.…”
Section: Effect Of Reboiling Of Water On Various Anionsmentioning
confidence: 99%
“…Thus on increasing the number of boiling stages, loss of water through evaporation operation can act as a thermodynamic driving force for the crystallization reaction resulting in the precipitation of insoluble salts (Gubbins 1997) onto the interior of the kettle (Figure 7). The continuous deposition of insoluble salts can reduce the heat transfer area and hence increases the power needed for the boiling operation (Gailani et al 2020). Whelton et al (2007) reported that the continuous deposition of mineral salts can affect the quality attributes of boiled water such as color and taste.…”
Section: Effect Of Reboiling Of Water On Various Cationsmentioning
confidence: 99%
“…The reduction in surface tension can reduce the solid-liquid contact angle and can improve the spread ability and wettability of liquid droplets on the heating surface. Al-Gailani et al [13] investigated the influence of heating and cooling rate and water composition on the kinetics of inorganic salt precipitation taking place when water is heated from ambient temperature up to its boiling point. They deposited a thin layer of liquid on a surface heated to 100 • C and the allowed it to cool down.…”
Section: Introductionmentioning
confidence: 99%